2019
DOI: 10.1136/bmjopen-2018-026297
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gastroschisis with maternal genitourinary infections: the US National birth defects prevention study 1997–2011

Abstract: ObjectiveTo assess the association between occurrence and timing of maternal self-reported genitourinary tract infection (urinary tract infections [UTIs] and/or sexually transmitted infection [STI]) and risk for gastroschisis in the offspring.DesignPopulation-based case–control study.SettingNational Birth Defects Prevention Study, a multisite study in the USA.ParticipantsMothers of 1366 gastroschisis cases and 11 238 healthy controls.Main outcome measuresCrude and adjusted ORs (aORs) with 95% CIs.ResultsGenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 60 publications
(72 reference statements)
2
29
1
5
Order By: Relevance
“…The prevalence of gastroschisis is higher in PUB hospitals, especially in the south. There is evidence that gastroschisis is associated with young maternal age (< 20 years) (Goldbaum et al 1990;Castilla et al 2008;Baer et al 2015) and probably with recurrent genitourinary infections in young women (Feldkamp et al 2019). In our study, maternal age under 20 was 14.5% and 17.4% in PUB-N and PUB-S hospitals, respectively, and 2.0% and 6.1% in PRI-N and PRI-S hospitals, respectively.…”
Section: Discussionmentioning
confidence: 43%
“…The prevalence of gastroschisis is higher in PUB hospitals, especially in the south. There is evidence that gastroschisis is associated with young maternal age (< 20 years) (Goldbaum et al 1990;Castilla et al 2008;Baer et al 2015) and probably with recurrent genitourinary infections in young women (Feldkamp et al 2019). In our study, maternal age under 20 was 14.5% and 17.4% in PUB-N and PUB-S hospitals, respectively, and 2.0% and 6.1% in PRI-N and PRI-S hospitals, respectively.…”
Section: Discussionmentioning
confidence: 43%
“…In a Canadian cohort study involving two large databases, smoking (odds ratio (OR), 2.86; 95% CI, 2.22–3.66), a history of pregestational or gestational diabetes (OR, 2.81; 95% CI, 1.42–5.5), and use of medication to treat depression (OR, 4.4; 95% CI, 1.38–11.8) emerged as significant associations with gastroschisis pregnancies [ 20 ]. The National Birth Defects Prevention Study 1997–2011 reported genitourinary tract infections during the periconceptional period to be significantly associated with gastroschisis (OR, 1.5; 95% CI, 1.3–1.9) [ 28 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The finding of zero cases of GS in the HB is not too surprising since the major risk factors such as low maternal age (less than 20 years), smoking, alcohol, illicit drug use, underweight (BMI less than 18), poor nutrition, genital infections (Baer et al, 2015; Bugge et al, 2017; Feldkamp et al, 2019; Rasmussen & Frías, 2008; Skarsgard et al, 2015) and opioid exposure (Short et al, 2019) are probably low in this population due to cultural, religious, and lifestyle patterns of the HB. Marriages do not occur until adult baptism has taken place, generally between the ages of 19 and 22 (Hostetler, 1985).…”
Section: Discussionmentioning
confidence: 99%